2010
DOI: 10.3171/2010.5.spine09813
|View full text |Cite
|
Sign up to set email alerts
|

Vertebroplasty-augmented short-segment posterior fixation of osteoporotic vertebral collapse with neurological deficit in the thoracolumbar spine: comparisons with posterior surgery without vertebroplasty and anterior surgery

Abstract: The results suggest that additional reinforcement with vertebroplasty reduces the kyphotic loss and instrumentation failure, compared with patients without the reinforcement of vertebroplasty. Vertebroplasty-augmented short-segment fixation seems to offer immediate spinal stability in patients with thoracolumbar osteoporotic vertebral collapse; the effect seems equivalent to that of anterior reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 41 publications
3
77
0
Order By: Relevance
“…In our previous study on thoracolumbar OVC, we reported that VP-augmented short-segment fixation seems to offer immediate spinal stability, and the effect seemed equivalent to that of anterior reconstruction. 26,28 Similar to low lumbar OVC, VP is available for the stability of the collapsed vertebra. However, VP without short fusion (only VP) is not recommended because the load on middle and/or posterior lesions of the affected vertebra increased in this group, and collapse of the affected vertebra could easily progress.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study on thoracolumbar OVC, we reported that VP-augmented short-segment fixation seems to offer immediate spinal stability, and the effect seemed equivalent to that of anterior reconstruction. 26,28 Similar to low lumbar OVC, VP is available for the stability of the collapsed vertebra. However, VP without short fusion (only VP) is not recommended because the load on middle and/or posterior lesions of the affected vertebra increased in this group, and collapse of the affected vertebra could easily progress.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this theory, several types of surgical decompression and fusion through either an anterior and/or posterior approach have been performed [1,12,15,19,26,31,34,37]. However, some authors have reported that conservative treatment could provide reliable neurologic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The results of percutaneous vertebral body augmentation in osteoporotic compression fractures (OCF) without trauma has encouraged surgeons to extend the indications and use these techniques to restore anterior column even in traumatic fractures as stand-alone intervention or in combination with posterior instrumentation [9,10,14-16,20,21,34,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations describe a higher risk of instrument failure in short segment instrumentation with increased preoperative kyphotic deformity in osteoporotic patients [21]. VP is considered to increase spinal stability in patients with thoracolumbar burst fractures, to decreases the instrument failure rate, and to improve postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation